Addressing Patient Loyalty Through Their Commitment Influenced by Electronic Word-of-Mouth and Hospital’s Image - Upe, Al Quadhri; Palilati, Alida; Zaid, Sudirman; Nasrul, Nasrul (UI Scholars Hub, 2024)
This article explores the influence of Electronic Word of Mouth (e-WoM) and hospital image on hospital patient loyalty, emphasizing the mediating role of patient commitment. Amidst the development of the healthcare industry sector in Indonesia, this study highlighted that e-WoM and hospital image significantly enhanced patient loyalty, with patient commitment playing an important mediating role. This article suggested practical strategies for hospitals, such as improving the quality of healthcare services, leveraging positive e-WoM, and implementing loyalty programs to elevate patient commitment and loyalty. These findings underscore the importance of hospital image and e-WoM in patient retention, providing valuable insights for strategic planning in the context of the healthcare industry.